Preferred Smoking Cessation Methods for Asian or Pacific Islander Household Smokers Who Live with Hospitalized Children - Lee, Meta T (University Clinical, Education & Research Associate (UCERA), 2011)
INTRODUCTION: A qualitative study was conducted to determine preferred smoking cessation methods among Asian or Pacific Islander (API) smokers who live with hospitalized children. This study occurred in a children's hospital where a new cessation program would be developed. METHODS: Twenty-six API smokers who live with children admitted to the hospital were interviewed and tape-recorded. Responses to survey questions were transcribed, categorized, and analyzed. RESULTS: 73% were interested in quitting, 34% within the next 30 days. Few would independently use the quit-line (31%) or attend group classes (4%). However, if offered during their child's hospitalization, 52% would sign up for individualized counseling and 29% would attend group sessions. Respondents believed advice would be helpful from their physician (71%), child's pediatrician (65%), nurse (64%), respiratory therapist (65%), or smoking cessation counselor (75%). CONCLUSIONS: The majority of API smokers were interested in quitting and receptive to one-on-one counseling. Advice would be helpful from any healthcare professional.